Efektifitas Terapi Relaksasi Nafas Dalam dan Dzikir terhadap Kadar Gula Darah pada Klien DiabetesTipe II di RS Mitra Medika Bondowoso - Handono Fatkhur Rahman; Vivi Aisyah; Heri Siswanto (Pustaka Kesehatan, 2023)
Along with the increase in type II diabetes mellitus cases, various efforts made to control blood sugar levels of patients with type II diabetes mellitus include nonpharmacological interventions in deep breathing relaxation and dzikir therapy need to be considered. In addition to being easy and practical, it can be used for daily therapy used by people with diabetes mellitus. The purpose of the study was to determine the effectiveness of deep breath relaxation therapy and dhikir for blood sugar levels in clients of Type II Diabetes Mellitus in the Hospital of Mitra Medika Bondowoso. The research design used a two-group type pretest-posttest design with a total sample of 70 people divided into 2 groups of 35 groups each and given a different intervention that is deep breathing relaxation and dhikr using the Saturated Sampling technique. Then analyzed by Paired t-test and One Way Anova statistical test with significance level α ≤ 0.05 to find out the comparison between two different groups. The results showed that p value = 0.209 (p> 0.05) which means there was nosignificant difference between deep breathing relaxation therapy and dhikr therapy, meaning that it was equally effective in reducing blood sugar levels in clients of Diabetes Mellitus. The conclusion is that deep breath relaxation therapy and dzikir are effective against blood sugar levels in clients of Type II Diabetes Mellitus in the Hospital of Mitra Medika Bondowoso.